Technical description of the U.K. large telescope - Davies, R; Raybould, K (Publ by Int Soc for Optical Engineering, 1990)
The UK is currently developing an 8m optical/infrared telescope in a Phase A program which started in October 1988. The design studies will be completed in September 1990 when a report will be submitted to the Science and Engineering Research Council for approval. This paper describes the telecope facility and briefly outlines the Phase A design studies. The technical effort during the Phase A has concentrated on aspects that require design efforts to prove technical feasibility, and on design areas that have a potentially high impact on the cost. The UK Large Telescope project is a national endeavour co-ordinated by the project team based at Oxford University and includes significant contributions from the Royal Greenwich Observatory, the Royal Observatory Edinburgh, the Rutherford Appleton Laboratory, the Council Works Unit, and several University groups.